Cartografia das controvérsias sobre “evidência científica” na saúde mental infantojuvenil no município de Fortaleza-CE - Souza, Nívia Tavares Pessoa de (2025)
Mental health in childhood and adolescence is a major challenge for public health policies, since the number of mental disorders in this population has increased and the difficulties in implementing the Child and Adolescent Mental Health (CAMH) policy in Brazil still persist. Given the complexity of this issue, this thesis questions whether it is possible to use scientific evidence to support CAMH policies in order to make them more effective. With this in mind, this work analyzed the CAMH policy scenario in Fortaleza, its actors, discourses and their implications for “scientific evidence”. To this end, a qualitative study was carried out. Secondary data was collected from the reports of the Health and Mental Health Conferences held in Fortaleza from 2001 to 2019, as well as an analysis of the minutes of the meetings of the Fortaleza Municipal Health Council (FMHC) from 2017 to 2021, the multi-year and health plans and the management reports for that period. Interviews were also conducted with spokespeople for the CAMH policy. Bruno Latour's actor-network theory, through the cartography of controversies, was used as a theoretical lens. The data was analyzed using discourse analysis by Michel Pechêux and Eni Orlandi. As a result, the conference reports identified a difficulty in recognizing children and adolescents as subjects of rights, and the lack of visibility of these actors in Mental Health (MH) policy. We also identified the coexistence of ideas and elements from the asylum and psychosocial models in the proposals. In the FMHC, discussions about CAMH were also scarce and, when they did take place, they focused on the structural problems of the CAPS, the lack of human resources and the disorganization of the RAPS. In the multi- annual plans, health plans and management reports, actions were identified regarding the creation of protocols and lines of care, which operationalize evidence in health policies; however, these actions were not carried out. The term “scientific evidence” was better understood by health professionals, who when describing it referred to concepts from their professional training and practice. Members of civil society, on the other hand, related evidence to scientific research. Therapeutic guidelines and evidence-based protocols were identified as guiding elements of public policy for safer and more effective practice, but there were difficulties in using them in services. Regarding the use of evidence to support CAMH policy, there was a consensus among the researchers that MH is a complex field, in which scientific evidence based on systematic reviews of randomized clinical trials is unable to cover, since it deals with the individual based on their subjectivity. We conclude that there is an invisibility of CAMH, since most discussions still focus on adult MH. The weaknesses of the RAPS, especially in terms of structure, make it difficult to implement MH policy in the municipality. There is a lack of discussion about “scientific evidence” and its effective incorporation, as well as the difficulty for actors to deal with this issue.